Cathelicidins Induce Toll-Interacting Protein Synthesis to Prevent Apoptosis in Colonic Epithelium - Ravi Holani; Chathurika Rathnayaka; Graham A.D. Blyth; Anshu Babbar; Priyoshi Lahiri; Daniel Young; Antoine Dufour; Morley D. Hollenberg; Derek M. McKay; Eduardo R. Cobo (Journal of Innate Immunity, 2022)
Cathelicidin peptides secreted by leukocytes and epithelial cells are microbicidal but also regulate pathogen sensing via toll-like receptors (TLRs) in the colon by mechanisms that are not fully understood. Herein, analyses with the attaching/effacing pathogen Citrobacter rodentium model of colitis in cathelicidin-deficient (Camp−/−) mice, and colonic epithelia demonstrate that cathelicidins prevent apoptosis by sustaining post-transcriptional synthesis of a TLR adapter, toll-interacting protein (TOLLIP). Cathelicidins induced phosphorylation-activation of epidermal growth factor receptor (EGFR)-kinase, which phosphorylated-inactivated miRNA-activating enzyme Argonaute 2 (AGO2), thus reducing availability of the TOLLIP repressor miRNA-31. Cathelicidins promoted stability of TOLLIP protein via a proteosome-dependent pathway. This cathelicidin-induced TOLLIP upregulation prevented apoptosis in the colonic epithelium by reducing levels of caspase-3 and poly (ADP-ribose) polymerase (PARP)-1 in response to the proinflammatory cytokines, interferon-γ (IFNγ) and tumor necrosis factor-α (TNFα). Further, Camp−/− colonic epithelial cells were more susceptible to apoptosis during C. rodentium infection than wild-type cells. This antiapoptotic effect of cathelicidins, maintaining epithelial TOLLIP protein in the gut, provides insight into cathelicidin’s ability to regulate TLR signaling and prevent exacerbated inflammation.